Auditoría financiera a la empresa INCOREG CÍA. ltda., de la ciudad de Riobamba en el período comprendido del 1 de enero al 31 de diciembre del 2015 - Villa Zavala, Myriam Alexandra (2017)
The present research work is aims to carry out a Financial Audit to the Company INCOREG Cía. Ltda., of the city of Riobamba in the period from January 1 to December 31, 2015; this process structured as follows: Firstly, the Referential Framework details the approach and formulation of the problem, the objectives to be archived and the justification of the audit work. In the state of the art related to the Thematic or theoretical Framework are the generalities of the Company and to the theoretical basis; which establishes the definitions of the Financial Audit, its objectives, characteristics, differences with other audits and phases of the Financial Audit, in addition to the Audit Standards Generally Accepted and their classification, finally discloses the Internal Control, the internal control and components. In the Methodology; the methods, techniques and investigative instruments, population and sample are detailed which were use in the examination. In the results and discussion; it is included the application of the phases, techniques and procedures of the Financial Audit. Finally, the conclusions and recommendations addressed to the Company´s officers are presented, after the analysis carried out, followed by the annexes; in which are reflected the financial statements provided by the Company.